The equation 9x^4+5x^2-4=0 has to be solved. Let y = x^2, this gives the equation

9y^2 + 5y - 4 = 0

=> 9y^2 + 9y - 4y - 4 = 0

=> 9y(y + 1) - 4(y + 1) = 0

=> (9y - 4)(y + 1) = 0

...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The equation 9x^4+5x^2-4=0 has to be solved. Let y = x^2, this gives the equation

9y^2 + 5y - 4 = 0

=> 9y^2 + 9y - 4y - 4 = 0

=> 9y(y + 1) - 4(y + 1) = 0

=> (9y - 4)(y + 1) = 0

=> y = 4/9 and y = -1

x^2 = 4/9

=> x = -2/3 and x = 2/3

x^2 = -1

=> x = -i and x = i

**The solution of the equation 9x^4+5x^2-4=0 is x = -i, x = i, x = -2/3 and x = 2/3**